2016
DOI: 10.3390/horticulturae3010007
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Performance of Horticultural Substrates—3. Impact of Substrate Composition and Ingredients

Abstract: Horticultural substrates, also referred to as growing media, potting soils and gardening or soilless substrates, are widely used as a basis for vegetable and flower production in horticulture. They are created as a composition of different ingredients (bog peat, organic residuals, coir, perlite and other components). Hydraulic properties such as water storage capacity, air capacity, shrinkage behaviour, wettability or hydraulic conductivity are important variables for a comprehensive evaluation of the performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
2
2
0
Order By: Relevance
“…These findings agree well for water retention functions of mineral and organic soils 14,15 and the unsaturated hydraulic conductivity measured with the HYPROP and the multi-step-outflow-method. 16 The results obtained in this study agree with previous studies 4, 5 and confirm findings presented in 13 the water retention curves of all tested natural mineral and organic soils and exemplarily of three horticultural substrates are illustrated in Figure 3. The easily plant available water (EAW) in the tension range between 20 and 100hPa 1,10 and the air capacity (Air) are marked in the Figure3.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These findings agree well for water retention functions of mineral and organic soils 14,15 and the unsaturated hydraulic conductivity measured with the HYPROP and the multi-step-outflow-method. 16 The results obtained in this study agree with previous studies 4, 5 and confirm findings presented in 13 the water retention curves of all tested natural mineral and organic soils and exemplarily of three horticultural substrates are illustrated in Figure 3. The easily plant available water (EAW) in the tension range between 20 and 100hPa 1,10 and the air capacity (Air) are marked in the Figure3.…”
Section: Resultssupporting
confidence: 91%
“…However, information to the hydraulic properties is missing of the substrate package. Until recently substrate buyers cannot draw any conclusions regarding the hydraulic properties on the basis of the declaration and the ingredients of the particular product he has bought, 1,[3][4][5] concluded that there is a lack of technologies and methods for the effective physical characterization and evaluation of substrate application in horticulture. The papers [3][4][5] are in the public domain.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the substrate with a high amount of compost (VC) showed a higher capacity to store water (AW, EAW, WBC) than VPC and VP. The PS substrates (VPC and VP) showed a higher air capacity and limited easily available water compared to the VC substrate [42]. This was also confirmed by the combination of Van Genuchten Equation with a predictive model for the unsaturated hydraulic conductivity in a combined hydraulic model [33].…”
Section: Discussionsupporting
confidence: 54%
“…Cities and their growing population tend to utilize resources from urban surroundings or the countryside to satisfy their needs. High-quality topsoils, for example, are imported from the countryside to be used for urban greening (Cannavo et al 2018;Deeb et al 2016b;Rokia et al 2014) or bog peat is used as main constituent of growing media (Schindler et al 2016). Thereby, functioning rural ecosystems and landscapes are exploited and disturbed.…”
Section: Introductionmentioning
confidence: 99%